Pertinencia en la evaluación del entorno de aprendizaje de la carrera de marketing de la Facultad de Ciencias Administrativas, Gestión Empresarial e Informática de la Universidad Estatal de Bolívar, durante los años 2013-2014 - Fuentes Garcia, Luis Alfredo (2015)
This research aims primarily to meet the indicator tracking graduates of the School of Marketing at the Faculty of Sciences Very necessary administrative criteria for the evaluation and decision-making Regarding the Improvement of the race. Today entire career should have a monitoring system graduates, which is why the vital need for the race count on Marketing it. This research is divided into three chapters the same as described below: In Chapter I, the topic is described, Background, Problem Statement, Justification, Objectives, Theoretical Framework which contains the Reference that is the history and important aspects of the College and Career; Geo Reference Location determining the completion of the work: that is the basis Legal legal environment in which the work is based; Conceptual Theory dealing terminology contains scientific theory; and scientific theory is the theoretical foundation the research topic divided into themes chosen following research and read different authors, Hypothesis, variables, operationalization described, Methodology and Sample Universe. Chapter II contains the collection of data by applying the respective surveys, Analysis and Interpretation of Results, Checking Hypothesis, Conclusions and Recommendations. Chapter III, the proposal, which is based on the completion of a report established tracking graduates for decision making in improving Academic Career Marketing.